Respostas

2014-05-01T19:39:36-03:00
Sabemos que  f(x) é f(1), devemos então substituir, na função f(x) 3x+1---> 3.1+1=4            
 e g(x) é g(1), agora substituindo G(x)=4x/5+a---> 4.1/5+a= 4/5+a

Agora resolvemos f(1) -g(1)=2/3------->4-4/5+a=2/3------>fizemos o mmc ---> a=2/3
1 5 1
2014-05-01T19:51:49-03:00
F(1) = 3.1 + 1 = 3 + 1 = 4
g(1) =4.1/5 + a = 4/5 + a   e   f(1) - g(x) = 2/3 ; então: 
4 - (4/5 + a) = 2/3 ⇒ 4 - 4/5 - a = 2/3;   mmc(3,5) = 15
60 - 12 -15a = 10 ⇒  60 - 12 - 10 = 15a ⇒  38 = 15a ⇒ a = 38/15

                              Resposta:   a = 38/15
6 4 6